A literal act of congress: reconciling conservation science and policy - Ballard, Jennifer R.; Booth, Austin T. (Frontiers in Conservation Science, 2025)
Modern conservation is a complex intersection of biological, physical, and social sciences applied to balance ecological needs and human interests within a defined regulatory framework; developing comprehensive policy recommendations that account for this complexity is challenging. New policy recommendations should be presented with adequate consideration for their scientific justifications, social implications and legal applications. Policy proposals that are not adequately contextualized risk undermining public trust and missing opportunities for advocacy; two examples are provided. Greater collaboration across the research and applied conservation disciplines, increased representation of environmental law and conservation policy expertise, and partnerships between schools of law and biological sciences could facilitate the advancement of more comprehensive policy proposals.